Effect of Moringa Leave Ethanol Extract on Accelerating Wound Healing Process - Jaya, Fidi Bhawana; Syamsunarno, Mas Rizky Anggun Adipurna; Sahiratmadja, Edhyana; Sulistiyorini, Ifa (Universitas Islam Bandung, 2023)
TGF-β and VEGF are vital in cell proliferation and regeneration, as evidenced in processes like wound healing. The leaves of Moringa oleifera Lam exhibit anti-inflammatory and cell regenerative properties that may facilitate the transition from the inflammatory to the proliferative phase, enhancing wound repair. This research sought to discern the potential of orally administered moringa leaf extract in augmenting systemic wound healing, focusing on TGF-β and VEGF serum as in vivo molecular markers. This research was conducted at the Animal Laboratory of the Faculty of Medicine, Universitas Padjadjaran, and the Laboratory of Molecular Genetics, Universitas Padjadjaran, from January to March 2022. We divided thirty Swiss Webster mice into two categories: healthy and wound-treated. Wounded mice received 100 mg/kgBW Na CMC as a negative control, 500 mg/kgBW zinc syrup as a positive control, and M. oleifera leaves ethanol extract (MOLE) in doses of 280 and 560 mg/kgBW orally from day 3 to day 6. Wound progression was documented and measured on days 0, -1, -3, and -6. Day-6 blood samples were obtained, and TGF-β and VEGF serum levels were gauged using ELISA. Results from day 6 revealed that wound coverage in the 280 and 560 mg/kgBW MOLE groups was 13.76±5% and 13.38±4%, respectively. These percentages notably surpassed that of the negative control group (p=0.005). However, the TGF-β and VEGF serum levels in the MOLE-treated groups did not differ significantly from the negative control (p=0.081 and p=0.149, respectively). Thus, the study concludes that while MOLE expedites wound closure, it does so without the systemic involvement of TGF-β and VEGF in vivo.